Effect of fermented Rhus verniciflua stokes extract on liver function parameters in healthy Korean adults: a double-blind randomized controlled trial - Jung Hyun Kwak (BMC, 2021)
Abstract Background Fermented Rhus verniciflua Stokes extract (FRVE) reported an anti-hepatic lipidemic property mediated by the upregulation of AMP-activated protein kinase (AMPK) in cell and animal models. However, it remains unclear whether there is an effect of FRVE on liver disease-related parameters and serum lipid levels in humans. We investigated the effects of FRVE intake for 12 weeks on liver disease-related parameters and serum lipid profiles in Korean adults. Methods A randomized, double-blind, placebo-controlled study was conducted among 79 subjects. An aqueous extract of fermented Rhus verniciflua Stokes that was filtered and fermented was prepared. For 12 weeks, the test group (n = 39) consumed two capsules of FRVE (main components: fustin 129 mg and fisetin 59 mg) once daily. The control group (n = 40) consumed two placebo pills (main component: lactose 627.0 mg) once daily. A 1:1 randomization of control and test was performed using computer-generated randomization. Both before and after FRVE intake, anthropometric parameters, liver function-related parameters, and clinical laboratory parameters were measured. The effects between the test and control groups were compared using the Mann-Whitney U test and independent t-test, and the difference between baseline and follow-up values was compared using Wilcoxon rank-sum test and paired t-test. Results There was no significant difference when comparing the change values of liver disease-related parameters and serum lipid profiles in between groups. Conclusions In our study, we did not confirm the significance in liver function parameters and serum lipid profiles. Trial registration The study protocol was registered in the Clinical Research Information Service (CRIS: https://cris.nih.go.kr/cris/index.jsp ) under number KCT0005687. Registered on 2 December 2020